Africa's Demographic Transition : Dividend or Disaster? - Canning, David; Raja, Sangeeta; Yazbeck, Abdo S. (Washington, DC: World Bank; and Agence Française de Développement, 2015)
This book lays out a range of policy actions that are needed at the various phases of the demographic transition and uses global and regional experiences to provide evidence on what has worked and what has not. Countries have a menu of options available to speed up the transition, improve investment in the resulting youth cohort, expand labor markets, and encourage savings. This book not only looks at lessons from East Asia, Latin America, and the Middle East, but also at unique demographic characteristics in Sub-Saharan Africa.